Exploring teachers' cultural perception of ICT in Nigerian schools through a qualitative approach - Uyouko, Arit Uyouko; Wong, Su Luan (UHAMKA Press, 2013)
The purpose of this study was to explore teacher’s cultural perception of ICT in Nigerian Schools. The study was guided by three research questions and used the qualitative method, with a case study as a strategy. Interviews were employed to collect data about teacher’s cultural perception of ICT in Nigerian schools. Findings from the interview revealed that teachers are incompetent and blame lack of ICT facilities and access for this inadequacy. All five participants demonstrated that their current ICT status did not match up with global standards. Findings also revealed reservations about software and materials on the internet as being inappropriate to norms and values of the country. Findings of this study are important for policy makers and stakeholders in the Nigerian education system.